THE IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN LEARNING FOREIGN LANGUAGES (Scientific journal of the Fergana State University, 2024)
This article analyzes the role of artificial intelligence technologies in the process of teaching and learning foreign languages. Compared to traditional teaching methods, artificial intelligence tools provide students with an individualized approach, create an interactive educational environment, and contribute to the development of language skills. The article also examines the innovative approaches of artificial intelligence in language learning, its linguodidactic aspects, and its advantages in the educational process.